V-Y anoplasty for iatrogenic anal stenosis: our initial experience in BSMMU (Bangladesh Medical Journal, 2014)
To date, ideal surgical management of anal stenosis has not been well defined. Different surgical options have been described in literature to treat anal stricture starting from partial lateral internal sphincterotomy to different flap anoplasties. For severe anal stenosis, advancement flaps are the only option and all the techniques show good result and patient satisfaction. We treated five cases of severe anal stenosis by V-Y anoplasty in Colorectal Surgery Unit of BSMMU. Here we have shown the clinical outcome of V- Y anoplas DOI: http://dx.doi.org/10.3329/bmj.v42i2.18986 Bangladesh Med J. 2013 May; 42 (2): 51-54